Cultural Communication and The Politics of Representation: Negotiating National Cultural Mission in Global Artificial Intelligence Practices - Ida Riaeni; Muhammad Iqbal Manshur; Mohd Zaini Abu Bakar (Jogjakarta Communication Conference (JCC), 2026)
The development of artificial intelligence (AI) has significantly influenced cultural communication and cultural representation at both national and global levels. This study employs a systematic literature review (SLR) to analyze recent literature from Malaysia and Indonesia related to AI, cultural representation, and cultural digitization. Findings indicate that AI functions as both a mediator and an actor in shaping digital cultural representation, facilitating the preservation of traditions, and generating negotiation in the politics of cultural representation. A synthesis of Malaysian and Indonesian literature highlights differences in focus: Malaysia emphasizes public interactivity and AI literacy, whereas Indonesia prioritizes the preservation of traditions and integration of local values. This article presents an SLR table, a conceptual framework diagram, and theoretical, practical, and methodological implications for research in cultural communication and digital technology.